Soft Skill: Its Urgency and Development at Islamic Higher Education - Sabri, Ahmad (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The success of a person in a career work is not only determined by his or her technical capability, but also the non-technical skills which is so called âsoft-skillsâ.Â It is an attitude which is exemplified among the cognitive and values in the interaction with people around. Several identified falures in the communityâs life indicate that many Islamic university graduates suffered from lack of ability to buildÂ harmonious relationship with the environment.Â Therefore, it is a high time for this institution to consistently instil some types of soft-skills on the parts of the students.Â The current study shares the urgent needs for developing studentsâ soft-skills for Islamic colleges and universities. The paper ends up with several conclusions while promoting some commitments to be held by the faculty development including: the identification of soft-skills that have already existed in the studentsâ minds and which need to be developed, the exploration of soft skills attributes for the next 5 years based on the inspiration or opinion of the stake holders and alumnaes, the setting of action plan for academic and non-cademic agendas, acting out the planned activities, as well as the sustainable blue-print of valid soft-skills.Â Copyright Â© 2014 by Al-Talim All right reserved